The Synergy of Artificial Intelligence and Digital Innovation Hubs in Driving Digital Innovation For MSMES - Eka Wahyu Kasih; Ngadi Permana; Mohammad Chaidir (Cahaya Abadi Publisher, 2024)
This study aims to explore the role of collaboration between artificial intelligence (AI) platforms and Digital Innovation Hubs (DIHs) in enhancing the digital transformation of SMEs. Digital transformation is key to ensuring the sustainability and competitiveness of SMEs in the digital age, yet many face challenges in adopting advanced technologies. Collaboration between AI and DIHs can offer solutions to overcome these barriers. AI platforms provide automation and data analytics capabilities, while DIHs offer technical support, training, and innovation facilities to assist SMEs in implementing technology. This study uses a qualitative literature review methodology to identify and analyze previous research related to this topic. The findings suggest that this collaboration can enhance productivity, operational efficiency, and market access for SMEs. However, challenges such as resource limitations, resistance to change, and digital readiness of SMEs are critical factors to consider in its implementation. This research provides valuable insights for policymakers, academics, and practitioners in designing strategies to accelerate the digital transformation of SMEs through collaboration between AI and DIHs.